STUDY OF TORQUE NONUNIFORMITY IN DOUBLE-ACTION HYDRAULIC ROTARY VANE MO-TORS - V. Yu. Savin; V. Yu. Ilyichev (Вестник Дагестанского государственного технического университета: Технические науки)
Abstract. Aim. Hydraulic rotary vane motors rely on the principle of torque maintained at a nominal pressure. In this case, the most important parameter of the torque is its nonuniformity. The problem of determining nonuniform torque in hydraulic motors having ten and twelve vanes is investigated with the aim of ensuring the maximum stability of this parameter.Method. Braking torque occurs on the vanes of hydraulic rotary vane motors due to the pressure of the working fluid on the stator; the theoretical expression for torque does not take the braking effect of the vanes into account. Therefore, an expression is compiled for the braking torque of the vanes with a type of stator curve that provides constant acceleration of the vane relative to the rotor.Results. Plots of changes in braking torques were constructed for 10- and 12-vane motors. Ratios of the minimum and maximum braking torques equal to 0.33 and 0.5 for motors with ten and twelve vanes, respectively, were obtained.Conclusion. The torque nonuniformity coefficients for hydraulic motors for the given parameters of d =11,6% and d = 8,8% for motors having ten and twelve vanes, respectively, were obtained. The results of the analysis of the obtained parameters indicate a slight increase in the nonuniformity of torque in a ten-vane motor. In this case, a decrease in the number of vanes leads to an increase in the mechanical efficiency of the hydraulic machine.